2007
DOI: 10.1007/s10483-007-1104-8
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle coagulation in a planar jet via moment method

Abstract: Large eddy simulations of nanoparticle coagulation in an incompressible planar jet were performed. The particle is described using a moment method to approximate the particle general dynamics equations. The time-averaged results based on 3000 time steps for every case were obtained to explore the influence of the Schmidt number and the Damkohler number on the nanoparticle dynamics. The results show that the changes of Schmidt number have the influence on the number concentration of nanoparticles only when the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Three prominent methods, i.e., making a prior assumption for the shape of the aerosol size distribution (Pratsinis 1988;Yu et al 2006), approximating the integral moment by an n-point Gaussian quadrature (McGraw 1997;Yu et al 2007), and assuming the pth-order polynomial form for the moments (Barrett and Jheeta 1996), have been evaluated and compared (Barrett and Webb 1998). In this article, we develop a new approach, Taylor expansion technique, to solve this problem.…”
Section: Theorymentioning
confidence: 99%
“…Three prominent methods, i.e., making a prior assumption for the shape of the aerosol size distribution (Pratsinis 1988;Yu et al 2006), approximating the integral moment by an n-point Gaussian quadrature (McGraw 1997;Yu et al 2007), and assuming the pth-order polynomial form for the moments (Barrett and Jheeta 1996), have been evaluated and compared (Barrett and Webb 1998). In this article, we develop a new approach, Taylor expansion technique, to solve this problem.…”
Section: Theorymentioning
confidence: 99%
“…Especially for turbulence, the flow is characterized by eddies with a wide range of length and time scales. As a result, the large eddy simulation (LES) of the filtering approach is used for solving the turbulent flow (Chan et al, 2008a;Dong & Chan, 2006;Yin et al, 2007;Yu et al, 2006Yu et al, , 2007aYu et al, , 2007b.…”
Section: Les For the Flow Fieldmentioning
confidence: 99%
“…Yu, Lin, Chen, and Chan (2006) ;Yu, Lin, and Xiong (2007a) ;Chan, Lin, Zhou, and Chan (2006) and Yu, Lin, and Chen (2007b) have taken an advantage of the assumption of log-normal distribution to simulate the particulate flow in a planar jet and a round jet. Upadhyay and Ezekoye (2003) evaluated a 1-point QMOM for combined aerosol growth law and found that 1-point scheme could give accuracy comparable with lognormal scheme.…”
mentioning
confidence: 99%
“…The numerical simulation showed that coherent structure dominates the distributions of particle number intensity, mass concentration, size distribution and polydispersity, and increases the diffusion of particles into the surroundings. As the Damköhler number (D a ) was introduced, Yu et al (2007b) found the larger the Damkohler number, the higher the polydispersity, which is shown in Fig. 3.…”
Section: Nanoparticle Coagulation In a Planar Jet Flowmentioning
confidence: 91%